Dietary supplementation of quebracho and chestnut tannins mix in rabbit: effects on live performances, digestibility, carcase traits, antioxidant status, faecal microbial load and economic value. Issue 1 (2nd January 2019) - Mancini, Simone; Moruzzo, Roberta; Minieri, Sara; Turchi, Barbara; Cerri, Domenico; Gatta, Domenico; Sagona, Simona; Felicioli, Antonio; Paci, Gisella
Abstract: The effects of dietary supplementation of tannins mix (quebracho and chestnut) in rabbit diet were evaluated for productive performances, health parameters and digestibility in order to quantify their practical utilisation in the rearing system. One-hundred and twenty Martini group hybrid rabbits of 30 days old were fed four different diets for 60 days. The diets were formulated as: basal diet (negative control, C), basal diet supplemented by 0.3% of tannins mix (T0.3), basal diet supplemented by 0.6% of tannins mix (T0.6) and basal diet supplemented with coccidiostat (positive control, CC). Live performances did not show any significant differences, moreover, no significant differences were observed for all carcase traits except for gastrointestinal tract ( p  = .015, lowest values for T0.3 diet). Also, digestibility of the feed and faecal microbial load was not influenced by tannins addition. Slight differences between the diets were detected in catalase and glutathione peroxidase concentrations in plasma, as a common trend was revealed with higher values of C than the other diets. From an economical point of view, T0.3 diet showed to be more profitable than CC and T0.6. Tannins addition might be taken into account as potential feed additive in rabbit feeds, as it does not affect negatively the productive performances, digestibility and induce a slight increase of antioxidant status. Highlights: On an economical point of view tannin diet showed to be more profitable than a diet added with coccidiostat. Addition of tannins in rabbits' feed did not affect negatively productive performances and digestibility. Tannins represent a valuable feed additive in rabbit farming as a slightly increase of antioxidant status was induced.